Ultrasonic Waves Regulate Antioxidant Defense and Gluconeogenesis to Improve Germination From Naturally Aged Soybean Seeds - Huang, Yutao; Mei, Gaofu; Fu, Xujun; Wang, Yang; Ruan, Xiaoli; Cao, Dongdong (Frontiers in Plant Science, 2022)
Soybean seed contain substantial triacylglycerols and fatty acids, which are prone to oxidation during storage, contributing to dramatical deterioration of seed vigor. The present study reports an ultrasonic waves treatment (UWT), which is a physical method capable of promoting the germination ability of aged soybean seeds by regulating the antioxidant defense and gluconeogenesis. Germination test revealed that UWT significantly increased the germination rate and seedlings establishment of soybean seeds stored for 12 months, although insignificantly impacting the vigor of fresh (stored for 1 month) and short-term stored (for 6 months) seeds. Further biochemical analysis revealed that UWT decreased the H2O2, O2- and malondialdehyde contents in the aged soybean seeds during early germination. Consistently, UWT prominently elevated the activities of superoxide dismutase, catalase and acetaldehyde dehydrogenase, as well as the corresponding gene expressions. Besides, the soluble sugar content of UWT was significantly higher than that of untreated aged seeds. Analysis of enzyme activity showed UWT significantly up-regulated the activities of several key enzymes in gluconeogenesis and the transcription levels of corresponding genes. Moreover, UWT enhanced the invertase activity within aged seeds, which responsible for catalyzing sucrose hydrolysis for forming glucose and fructose. In summary, UWT improved germination and seedlings establishment of aged soybean seeds by regulating antioxidant defense and gluconeogenesis. The present study expand the application of ultrasonication in agricultural production, and further clarify the physiological and molecular mechanisms of aged seed germination, aiming to provide theoretical and practical guidance for seed quality and safety.